Biomechanical loading in the triple jump - Perttunen, J.; Kyröläinen, H.; Komi, P. V.; Heinonen, A. (Journal of Sports Sciences, 2000)
The triple jump is a demanding field event in which a jumper must tolerate extremely high impact forces while maintaining high horizontal speed. The present study was designed to clarify the mechanical loading characteristics and the role of neuromuscular function in the triple jump. Seven national triple jumpers (4 males, 3 females) volunteered to perform 3-6 jumps. The mean best performances were 14.32 ± 0.45 m and 11.90 ± 0.28 m for males and females, respectively. The three longest triple jumps for each jumper were selected for final analysis. The mean contact times were 0.139 s (hop), 0.157 s (step) and 0.177 s (jump). The largest ground reaction forces were observed in the step (15.2 times body weight), while the highest peak pressures were recorded under the heel and forefoot. The plantar pressure of the lateral side of the forefoot was highly related to the length of the triple jump (P < 0.05-0.01). In addition, electromyograms of both legs suggested that mechanical loading places high demands on the neuromuscular system, as characterized by the high rate of activation in the pre-activity phase followed by high eccentric activity. Thus, the high activities of the gastrocnemius, vastus lateralis and hip extensor muscles seem to play an important role in preventing unnecessary yielding of the jumper during the braking phase.